Management of The Implementation of The National Curriculum Based on Islamic Boarding School Education To Improve The Quality of Madrasah Aliyah (Descriptive Analytical Study at MA Al-Masthuriyah, MA Sunanul Huda, MA Al-Amin, Sukabumi Regency) - Irman Irman; Iim Wasliman; Waska Warta; Sayid Muhammad Rifky Naufal (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
One of the efforts to improve the quality of education is the application of a curriculum that is in accordance with the needs and developments of the times. Reality shows that the practice of national education with a curriculum that is made and structured in such a way has even been refined many times, has not been able to present an Indonesian human figure with a complete personality.Efforts to achieve the quality of education as expected by all components of the nation have been carried out, including by issuing various policies that support both from an institutional perspective, human resources and the operationalization of quality implementation in schools and madrasas, including Law no. 20 of 2003 concerning the National Education System, Law no. 14 of 2005 concerning Teachers and Lecturers and PP No. 19 of 2005 concerning National Education Standards, and most recently the Minister of Education and Culture of the Republic of Indonesia Number 28 of 2016 which states that Education Quality Assurance is a systematic, integrated and sustainable mechanism to ensure that the entire process the implementation of education is in accordance with quality standards. Islamic boarding school-based schools such as MA Al-Masthuriyah, MA Sunanul Huda and MA Al-Amin in Sukabumi Regency implement education by combining general education and religious education into one curriculum building. With this approach, all formal school subjects and activities cannot be separated from the frame of teachings and messages of Islamic values. There is no dichotomy, separation, and secularization where lessons and all discussions are separated from Islamic values and teachings, or "sacredization" where Islam is taught regardless of the context of the benefit of present and future life. Based on the phenomenon above, the researcher is interested in conducting research on the Application of Islamic Boarding School-Based National Curriculum Management to Improve the Quality of Madrasah Aliyah (Analytical Descriptive Study at MA Al-Masthuriyah, MA Sunanul Huda and MA Al-Amin, Sukabumi Regency). This study aims to examine the management of the implementation of the national curriculum at Islamic boarding schools based on Madrasah Aliyah. The approach used in this study is a qualitative approach. The method used is descriptive analytical method, in which the researcher will describe and then analyze in depth the research findings. Sallis stated, to measure quality education, of course, criteria/indicators are needed. Sallis revealed that there are many indicators of good quality in educational institutions, including: 1) upholding moral values; 2) very satisfactory test results; 3) support from parents, place of business and the surrounding environment; 4) abundant resources; 5) application of the latest technology; 6) strong leadership and clear vision; 7) care and concern for students; 8) a balanced and relevant curriculum. Based on the findings, interpretations and discussion, the general conclusion regarding Management of Implementation of the National Curriculum Based on Islamic Boarding School Education at MA Al-Masthuriyah, MA Sunanul Huda, MA Al Amin has been implemented, but has not yet had an optimal impact. The management of implementing the national curriculum based on Islamic boarding schools is still constrained by internal and external constraints. The internal obstacle is the low understanding, skills and motivation to make improvements to the curriculum itself because the teacher's understanding of the integrated curriculum is still not optimal. External constraints are also marked by the low level of supervision from the local Ministry of Religion.